+0

# Simplify

0
234
2

Simplify. Is this correct?

My answer = c^2 + d^2

Guest Mar 10, 2015

#3
+19207
+10

$$\small{\text{  \dfrac{ \dfrac{c}{d}-\dfrac{d}{c} } { \dfrac{1}{c}-\dfrac{1}{d} } = \dfrac{ \dfrac{c^2-d^2}{dc} } { \dfrac{d-c}{dc} } = \left( \dfrac{c^2-d^2}{dc} \right) \cdot \left( \dfrac{dc}{d-c} \right) = \dfrac{c^2-d^2}{d-c} = -\dfrac{c^2-d^2}{c-d} = -\dfrac{(c-d)\cdot (c+d) }{c-d} = - (c+d) }}\\\\$$

heureka  Mar 11, 2015
Sort:

#3
+19207
+10

$$\small{\text{  \dfrac{ \dfrac{c}{d}-\dfrac{d}{c} } { \dfrac{1}{c}-\dfrac{1}{d} } = \dfrac{ \dfrac{c^2-d^2}{dc} } { \dfrac{d-c}{dc} } = \left( \dfrac{c^2-d^2}{dc} \right) \cdot \left( \dfrac{dc}{d-c} \right) = \dfrac{c^2-d^2}{d-c} = -\dfrac{c^2-d^2}{c-d} = -\dfrac{(c-d)\cdot (c+d) }{c-d} = - (c+d) }}\\\\$$

heureka  Mar 11, 2015
#4
0

Thanks. That's the answer I also got, when I tried it the second time. :)

Guest Mar 11, 2015

### 10 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details